Perbanyakan Ruskus (Ruscus hypophyllum L.) secara In Vitro - Agus Purwito; Prima Muklisa; Awang Maharijaya (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2005)
These experiments were aimed to obtain optimum medium for micropropagation of Ruscus. There were two experiments consist of in vitro shoots proliferation, shoot elongation and rooting. The experiment of shoot proliferation performed by inducing adventitious shoots from explant in the Murashige and Skoog (1962)(MS) basal medium supplemented with combination of plant growth regulators BAP (0.0, 0.5, 1.0, 2.0, 4.0 and 6.0 mg/l) and IAA (0.0, 0.1, 0.2 and 0.4 mg/l). The elongation and rooting of plantlets were induced in the different concentration of the MS basal medium (0.5, 1.0 and 2.0 strength) combined with IBA (0.0, 1.0, 2.0, 3.0 and 4.0 mg/l). Both experiments were arranged as completely randomized design with 15 replications. Adventitious shoots were produced in all medium supplemented with BAP with or without IAA. However MS medium supplemented with BAP 1 mg/l or 2 mg/l combined with IAA 0.2 mg/l were the best. The number of adventitious shoots in these medium were 9.2 and 9.4 shoots after 8 weeks cultured respectively. Increasing concentration of BAP more than 4 mg/l decreased number and size of adventitious shoots. The plantlets produced in the proliferation medium were then transferring to the next treatments for elongation and rooting. The best medium for elongation and rooting were medium with half strength of MS with or without IBA. Acclimatization conducted by transferring the rooted plantlets on the medium containing sterilized soil and rice husk charcoal (1:1). After 4 weeks acclimatization, 60-100 percent of plantlets were survived and growth, depend on treatments. Key words: Acclimatization, adventitious shoot, micropropagation, rooting, Ruscus hypophyllum L.